2014
DOI: 10.3390/s140917089
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Prediction of Experimental Jump and Pull-In Dynamics in a MEMS Sensor

Abstract: The present research study deals with an electrically actuated MEMS device. An experimental investigation is performed, via frequency sweeps in a neighbourhood of the first natural frequency. Resonant behavior is explored, with special attention devoted to jump and pull-in dynamics. A theoretical single degree-of-freedom spring-mass model is derived. Classical numerical simulations are observed to properly predict the main nonlinear features. Nevertheless, some discrepancies arise, which are particularly visib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The non-linear dynamic behavior can therefore lead to jump phenomena and instabilities like the dynamic pull-in (see [17] , [18] and [19] ) which are critical for the accelerometer functioning.…”
Section: A)mentioning
confidence: 99%
“…The non-linear dynamic behavior can therefore lead to jump phenomena and instabilities like the dynamic pull-in (see [17] , [18] and [19] ) which are critical for the accelerometer functioning.…”
Section: A)mentioning
confidence: 99%
“…4c, when operating the resonator in the linear regime, a concentration of 3260 ppm shifts the first mode frequency by 1.78 kHz and the third mode by 2.455 kHz. To experimentally demonstrate the concept of smart switching, we fix the first source frequency at Ω1=68 kHz (first mode) and voltage amplitude VAC1 = 50 V, the second source frequency at Ω2=344 kHz (third mode) and voltage amplitude VAC2 = 40 V, and use VDC = 30 V. Ruzziconi et al [21] demonstrated that the stability of the resonator at a particular operating frequency depends on the size of the safe basin of attraction. As the driving frequency approaches the bifurcation frequency, the safe basin of attraction gets eroded and shrinks in size.…”
Section: Multi-modal Smart Switchingmentioning
confidence: 99%
“…However, when the vibration amplitude is close to or even located in the nonlinear region, instability caused by nonlinear effects will emerge and the overall sensor performance will be decreased [3,4]. Therefore, studies on the nonlinear dynamics of microresonators have been a research hot spot in recent years [5,6,7,8]. Obtaining the nonlinear dynamics by experimental methods will not only benefit in operating circuit configuration for the manufactured microsensors, but also provide guidance for future resonator design optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining the nonlinear dynamics by experimental methods will not only benefit in operating circuit configuration for the manufactured microsensors, but also provide guidance for future resonator design optimization. Furthermore, experimentally obtained nonlinear dynamic parameters provide reliable support for realizing the parameter resonance of microresonators employing the nonlinear characteristics [5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%